2023
DOI: 10.3390/ma16031311
|View full text |Cite
|
Sign up to set email alerts
|

ZnTe Crystal Multimode Cryogenic Thermometry Using Raman and Luminescence Spectroscopy

Abstract: In this study, ZnTe crystal was applied to provide precise thermal sensing for cryogenic temperatures. Multiple techniques, namely Raman and photoluminescence spectroscopies, were used to broaden the operating temperature range and improve the reliability of the proposed thermometers. Raman-based temperature sensing could be applied in the range of 20–100 K, while luminescence-based thermometry could be utilized in a narrower range of 20–70 K. However, the latter strategy provides better relative thermal sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…44 It was found that the 2 H 11/2 -4 I 15/2 transition, which is usually used as the transition from the upper thermal level in Er 3+ ions (DE E 800 cm À1 ), is hardly detected at low temperatures. [45][46][47] To perform precise temperature detection in the cryogenic range, which is of crucial importance in the fields of super-conducting magnets, aerospace, and macromolecular crystallography, [48][49][50][51] DE between thermally coupled energy levels should be smaller to respond to minimal temperature variations in low or ultralow temperature environments. The upconversion perovskite Na 0 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 It was found that the 2 H 11/2 -4 I 15/2 transition, which is usually used as the transition from the upper thermal level in Er 3+ ions (DE E 800 cm À1 ), is hardly detected at low temperatures. [45][46][47] To perform precise temperature detection in the cryogenic range, which is of crucial importance in the fields of super-conducting magnets, aerospace, and macromolecular crystallography, [48][49][50][51] DE between thermally coupled energy levels should be smaller to respond to minimal temperature variations in low or ultralow temperature environments. The upconversion perovskite Na 0 .…”
Section: Introductionmentioning
confidence: 99%
“…To perform precise temperature detection in the cryogenic range, which is of crucial importance in the fields of superconducting magnets, aerospace, and macromolecular crystallography, 48–51 Δ E between thermally coupled energy levels should be smaller to respond to minimal temperature variations in low or ultralow temperature environments. The upconversion perovskite Na 0 .…”
Section: Introductionmentioning
confidence: 99%
“…Time-dependent frequency shift and the evolution of the bandwidth in the excited state are correlated with anharmonicity [6]. It has been reported that multimode optical thermal sensors in the cryogenic temperature range are applied for thermometry using the concept of the frequency shift in the variation of the temperature due to the anharmonicity of the ZnTe [7]. The anharmonicity of the system plays a significant role in temperature-dependent quasi-particle interactions such as exciton-phonon and electron-phonon to push the limit of performance of devices at nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…The great majority of luminescence thermometers that have been investigated so far rely on a single parameter to deliver an accurate temperature reading. The utilization of multiple thermometric parameters within the context of multimodal [19][20][21][22][23] or the multiparametric approach [24][25][26][27][28], on the other hand, has the potential to enhance the performance of thermometers. So far, the advantage of multiparametric thermometry has been realized through the application of multiple linear regression or similar statistical techniques and artificial neural networks [10,29,30].…”
Section: Introductionmentioning
confidence: 99%